Langkah Awal Cegah Penyakit Metabolik dan Hipertrigliserida melalui Skrining Kadar Trigliserida di Kelurahan Tanjung Duren Selatan - Lamhot Asnir Lumbantobing; Alexander Halim Santoso; Edwin Destra; Valentino Gilbert Lumintang; Cristian Alexandro; Juan Edbert (PPNI UNIMMAN, 2025)
Triglycerides are an important metabolic indicator associated with the risk of metabolic syndrome and cardiovascular disease. Hypertriglyceridemia often develops without symptoms but contributes to the accumulation of atherogenic lipids. This activity involved 104 adult participants who underwent triglyceride level examination using Point-of-Care Testing (POCT). Education was delivered individually using a leaflet containing information on the relationship between high-calorie food intake and increased triglyceride levels, as well as recommendations for replacing energy-dense foods with healthy foods. A total of 47.1% of participants showed triglyceride levels ≥150 mg/dL, while the other 52.9% had normal levels. The average triglyceride level of 159.1 mg/dL reflects the hidden metabolic risk in the population. Education was provided based on the results of the examination to encourage the selection of low-calorie foods and increased fiber consumption. Triglyceride level examination is useful as an early screening for hypertriglyceridemia in the community. Education about high-calorie food consumption plays an important role in reducing metabolic risk and supporting the prevention of cardiovascular disorders through a healthier diet.